2014
DOI: 10.1007/s00270-014-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

Sac Angiography and Glue Embolization in Emergency Endovascular Aneurysm Repair for Ruptured Abdominal Aortic Aneurysm

Abstract: Purpose The purpose of this study was to demonstrate a sac angiography technique and evaluate the feasibility of N-butyl cyanoacrylate (NBCA) embolization of the ruptured abdominal aortic aneurysm (AAA) sac in emergency endovascular aneurysm repair (EVAR) in hemodynamically unstable patients. Methods A retrospective case series of three patients in whom sac angiography was performed during emergency EVAR for ruptured AAA was reviewed. After stent graft deployment, angiography within the sac of aneurysm (sac an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, the polymerization of NBCA starts immediately upon contact with anions, and it makes a permanent cast of the vessel, independent of inherent coagulation. 4 Regarding the amount and concentration of NBCA in this procedure, Koike et al 17 used 1 mL of a 50% mixture of NBCA and iodized oil. In our experience, we had difficulty delivering the catheter to the rupture site; thus, we had to inject a considerable amount of NBCA to seal the rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the polymerization of NBCA starts immediately upon contact with anions, and it makes a permanent cast of the vessel, independent of inherent coagulation. 4 Regarding the amount and concentration of NBCA in this procedure, Koike et al 17 used 1 mL of a 50% mixture of NBCA and iodized oil. In our experience, we had difficulty delivering the catheter to the rupture site; thus, we had to inject a considerable amount of NBCA to seal the rupture.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several authors have reported that sac embolization using embolic materials such as coils and thrombin during elective EVAR was useful in preventing type II endoleaks. [9][10][11][12][13][14][15][16] Several years ago, Koike et al 17 reported an initial experience with embolization of ruptured AAAs using N-butyl cyanoacrylate (NBCA) in 3 emergency EVAR cases. 17 At that time our group hypothesized that sac embolization using NBCA could be useful not only to prevent type II endoleaks but also to seal the rupture site.…”
Section: Introductionmentioning
confidence: 99%
“…NBCA can be effectively used, even in cases of emergency EVAR, for treating ruptured AAA with coagulopathy abnormalities [10]. In this case, hemostasis was achieved, although only the proximal part of the endoleak cavity close to the iliac limb stent graft was embolized.…”
Section: Discussionmentioning
confidence: 85%
“…9) Although there are remaining issues, such as the complicated nature of the procedure, selection of an embolic material, and endpoints, this procedure is promising as a solution in these cases. When persistent bleeding is suspected, blood transfusions and supplemental clotting factors for functional hemostasis and prompt re-evaluation with CECT are essential.…”
Section: Resultsmentioning
confidence: 99%